Genotoxic Assessment of the Dry Decoction of Myracrodruon urundeuva Allemão (Anacardiaceae) Leaves in Somatic Cells of Drosophila melanogaster by the Comet and SMART Assays. (3rd October 2019) - de Amorim, Érima Maria; de Santana, Samuel Lima; da Silva, André Severino; de Aquino, Nayara Coriolano; Silveira, Edilberto Rocha; Ximenes, Rafael Matos; Rohde, Claudia
Abstract : Medicinal plants are worldwide used as an efficient treatment of many diseases. Myracrodruon urundeuva Allemão (Anacardiaceae) is widely used Brazilian folk medicine to treat inflammations and infections of the female genital tract, conditions of the stomach and throat, and to heal wounds on the skin and mucous membranes. Several pharmacological properties of extracts and compounds isolated from M. urundeuva are found in the literature, corroborating its uses as antiulcer and gastroprotective, anti‐inflammatory and analgesic, as well as antimicrobial. Despite these many uses in traditional herbal medicine, there are few reports of its toxic‐genetic effect. This work aimed to investigate the genotoxic and mutagenic potential in vivo of the dry decoction of M. urundeuva leaves on somatic cells of Drosophila melanogaster, through the Comet assay and somatic mutation and recombination test (SMART). Six concentrations (0.5, 1.0, 2.0, 4.0, 8.0, and 16.0 mg/mL) were studied after feeding individuals for 24 hr in culture medium hydrated with extracts of M. urundeuva . In the Comet assay, all concentrations showed a genotoxic effect significantly higher than the negative control group, treated with distilled water. The two highest concentrations were also superior to the positive control group, treated with cyclophosphamide (1 mg/mL). In the SMART, there was a mutagenic effect at all concentrations tested, with a clear dose‐dependent relationship. Both recombination and mutation account for these mutagenic effects. The set of results indicate that the dry decoction of M. urundeuva leaves is genotoxic and mutagenic for D. melanogaster under the experimental conditions of this study. Environ. Mol. Mutagen. 61:329–337, 2020. © 2019 Wiley Periodicals, Inc.